Caracterização morfoagronômica e fenológica de dois acessos de Passiflora foetida L. - Silva, Misael Bruno de Araújo (Universidade Federal Rural do Semi-Árido, 2019)
Passionflower (Passiflora foetida L.) has been used as a rootstock for yellow passion fruit in the Northeastern region. However, there is little information on the phenological behavior and morphological characterization of the species, which will help to study genetic improvement programs. functional, medicinal and ornamental food. In this sense, the objective of this work was to evaluate the phenology of the species and the morphoagronomic characterization of two accessions of the species Passiflora foetida L. In the study of the phenology 10 plants of each access of P. foetida were evaluated for the development of the floral bud until the anthesis and from this until the maturation of the fruit, types of curvature of the stylet, stigma fertility, time of opening of the flower and floral visitors. In the morphoagronomic characterization the leaves, flowers and fruits were analyzed. It was verified that the development of the floral bud until anthesis lasted for 15 days and the anthesis until the fruit formation was 60 days. The two accessions present the three types of stilettos (without curvature, partially curved and totally curved), with more predominance of the fully curved stylet, and the floral visitors present in the area, the mamangava is the natural pollinator of the species. The morphoagronomic differences were observed in the leaves, flowers and fruits of the two accessions.
Monografia
Keywords: Maracujazeiro selvagem; Porta-enxerto; Melhoramento genético; Wild passion fruit; Rootstock; Genetical enhancement; CIENCIAS AGRARIAS::AGRONOMIA